An Examination of Strategic Alignment Mechanisms in Public Service Organisations - Sinz, Soeren (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2023)
Strategic alignment (i.e., the alignment between business and information and communications technology (ICT)) has remained a top management concern for decades – evident by the annual ICT issue survey published for executives (Ball & Harris, 1982; Niederman et al., 1991; Luftman & Mclean, 2004; Luftman & Ben-Zvi, 2010; Kappelman et al., 2020). While information systems research reflects deep engagement with the topic of strategic alignment, this thesis argues that the theoretical, methodological and philosophical positions taken have obfuscated the dynamic and complex nature of strategic alignment. As such, the thesis adopts a processual position to illustrate ‘how’ alignment emerges and develops over time as opposed to the dominant content perspective that seeks to answer ‘what’ needs to be aligned. The thesis therefore commences by outlining the concept of alignment delineating the historical footprints of the concept within systems theory, organisation theory, strategic management theory and finally, information systems research. In doing so, a case is made that the concept has been shaped by dominant perspectives in those domains and this influences how it has been adapted and deployed within information systems research. Finally, the conceptual lens adopted seeks to make a distinction between structural, social and technical components of strategic alignment to offer a more holistic perspective on the relationship between business and ICT. To facilitate the processual inquiry in alignment, a critical realist position is adopted which emphasises process metaphysics and a mechanism-based explanation of phenomena while deploying a single case study method due to its ability to capture context and ‘reality in flight’. The study uses the Irish Department of Foreign Affairs as a case organisation by tracing the development process of its ICT2020 Strategy over time – while also presenting prior business-ICT context spanning two decades to inform the current state of affairs. Grounded theory coding is used to capture themes and identify subsequent mechanisms, which are presented in an explanatory framework that encapsulates structural, social and technical alignment mechanisms across the discovery, formation and execution phases. The final chapter offers both contributions to academia and professional practice. The contribution to academia emphases the theoretical contribution by offering a processual understanding of strategic alignment and offers a steppingstone for further research as well as the empirical contribution of the case study itself. While the emphasis is to contribute to theory, several relevant actions and ideas relevant to professional practice are identified in the forms of collaborative and democratic approaches to strategising as well as learning and development to shape strategy formation.
APPROVED
Keywords: Strategic Alignment; Process Theory; Critical Realism; Strategic Information Systems